2019
DOI: 10.3390/ma12152418
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Polycarbonate by an Atmospheric Pressure Argon Microwave Plasma Sheet

Abstract: The specific properties of an atmospheric pressure plasma make it an attractive tool for the surface treatment of various materials. With this in mind, this paper presents the results of experimental investigations of a polycarbonate (PC) material surface modification using this new type of argon microwave (2.45 GHz) plasma source. The uniqueness of the new plasma source lies in the shape of the generated plasma—in contrast to other microwave plasma sources, which usually provide a plasma in the form of a flam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 65 publications
(110 reference statements)
0
13
0
Order By: Relevance
“…In this regard, Shaw and Czylkowskihave successfully applied atmospheric-pressure plasma in their studies to generate polar bond on the surface of polypropylene (PP) and polycarbonate (PC) material, respectively. 26,27 Among all nanoparticle synthetic methods, ionic gelation was applied for the synthesis of nano Cur-chitosan-TPP in this study, because this is a simple method and does not need any organic solvent and high temperature during the procedure. [28][29][30] However, Mirnezhad et al had synthesized nanoparticles using this method that was 160 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Shaw and Czylkowskihave successfully applied atmospheric-pressure plasma in their studies to generate polar bond on the surface of polypropylene (PP) and polycarbonate (PC) material, respectively. 26,27 Among all nanoparticle synthetic methods, ionic gelation was applied for the synthesis of nano Cur-chitosan-TPP in this study, because this is a simple method and does not need any organic solvent and high temperature during the procedure. [28][29][30] However, Mirnezhad et al had synthesized nanoparticles using this method that was 160 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the effect of CAP treatment on the modification of curcumin showed that the highest solubility was obtained at 50 ppm of CAP‐treated curcumin after the 90 s. Recently, enhancing the solubility of materials by CAP has attracted a big interest among researchers and various studies have been performed to achieve this aim. In this regard, Shaw and Czylkowskihave successfully applied atmospheric‐pressure plasma in their studies to generate polar bond on the surface of polypropylene (PP) and polycarbonate (PC) material, respectively 26,27 …”
Section: Discussionmentioning
confidence: 99%
“…As such, microwave treatment has received tremendous research interest in the synthesis and modication of materials. [40][41][42][43][44] For example, Liu et al thermally treated bamboo-based activated carbon using microwave radiation in N 2 for minutes, generating an activated carbon sample with increased C-O and less C]O, thus getting a better methylene blue adsorption performance. 45 However, most of the current work only applied microwave irradiation under atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue consists of five research papers and one review paper in which fundamental properties of APP have been explored to advance our understanding of plasma complex interactions [ 2 , 3 , 4 ] in which APP was ignited using novel plasma source designs [ 2 , 5 ] and has been used in a wide range of applications, particularly in nanofabrication [ 2 , 3 , 6 ], biocatalysts immobilization [ 7 ], and energy-related processes [ 2 ].…”
mentioning
confidence: 99%
“…In another study of plasma-material modification, Czylkowski et al [ 5 ] developed and constructed a new type of microwave plasma source. This APP source’s unique feature, in comparison to others, is the shape of the plasma generated, in which it extends into the air and forms a sheet-like shape.…”
mentioning
confidence: 99%